2022
DOI: 10.16993/tellusa.44
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Dependencies at Monthly and Interannual Time Scales in the Climate System: Study of the North Pacific and Atlantic Regions

Abstract: The directional dependencies of different climate indices are explored using the Liang-Kleeman information flow in order to disentangle the influence of certain regions over the globe on the development of low-frequency variability of others. Seven key indices (the sea-surface temperature in El-Niño 3.4 region, the Atlantic Multidecadal Oscillation, the North Atlantic Oscillation, the North Pacific America pattern, the Arctic Oscillation, the Pacifid Decadal Oscillation, the Tropical North Atlantic index), tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
7
18
0
Order By: Relevance
“…out what happens at interannual and decadal time scales, we take the 12-month and 120-month running mean SST and THF, respectively, and re-compute the rate of information transfer in the 3D case (SST, SST tendency and THF). This approach is similar to the one used in Vannitsem and Liang (2022), who found differences in the rate of information transfer between climate indices depending on the time scale used.…”
Section: Interannual To Decadal Variabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…out what happens at interannual and decadal time scales, we take the 12-month and 120-month running mean SST and THF, respectively, and re-compute the rate of information transfer in the 3D case (SST, SST tendency and THF). This approach is similar to the one used in Vannitsem and Liang (2022), who found differences in the rate of information transfer between climate indices depending on the time scale used.…”
Section: Interannual To Decadal Variabilitymentioning
confidence: 96%
“…This novel method has been successfully applied to several climate studies, e.g. causal influences between greenhouse gases and global mean surface temperature (Stips et al, 2016;Jiang et al, 2019), dynamical dependencies between a set of observables and the Antarctic surface mass balance (Vannitsem et al, 2019), soil moisture -air temperature interactions in China (Hagan et al, 2019), prediction of El Niño Modoki (Liang et al, 2021), causal links between climate indices in the North Pacific and Atlantic regions (Vannitsem and Liang, 2022), and identification of potential drivers of Arctic sea-ice changes (Docquier et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These are often expressed in terms of correlations between the tropical and extratropical regions, suggesting a potential influence on one another. Note however than correlation does not mean causation as already stressed in many recent works on causality analyses [6][7][8][9]. In [9], a new approach of causality detection was used to clarify the transfer of information among different climate indices and in particular ENSO on monthly to decadal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Note however than correlation does not mean causation as already stressed in many recent works on causality analyses [6][7][8][9]. In [9], a new approach of causality detection was used to clarify the transfer of information among different climate indices and in particular ENSO on monthly to decadal time scales. It was in particular shown that ENSO has considerable influence on the Pacific North Atlantic pattern, on the Pacific decadal oscillation, on the tropical North Atlantic region and slightly on the Arctic oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…This novel method has been successfully applied in several climate studies, e.g. causal influences between greenhouse gases and global mean surface temperature (Stips et al, 2016;Jiang et al, 2019), the dynamical dependence between a set of observables and the Antarctic surface mass balance (Vannitsem et al, 2019), soil moisture -air temperature interactions in China (Hagan et al, 2019), prediction of El Niño Modoki (Liang et al, 2021), causal links between climate indices in the North Pacific and Atlantic regions (Vannitsem and Liang, 2022), identification of potential drivers of Arctic sea-ice changes (Docquier et al, 2022b), and ocean-atmosphere interactions (Docquier et al, 2022a).…”
mentioning
confidence: 99%